Evaluación de la integridad de anticuerpos IGY dirigidos contra las cepas vacunales E. COLI K99 y parvovirus canino aislados a partir de yema de huevo de gallina - posible uso terapéutico (2022)
A chicken egg is the largest biological cell known and is made up of of several important chemicals. It is a reservoir of variable nutrients, proteins, lipids, carbohydrates and other biologically active substances including growth promoting factors that are needed to produce a chicken (Kim et al. al., 2000). Within the group of egg proteins, are the immunoglobulins that predominate in the yolk of the egg and that are responsible for passive immunity in the birds. These immunoglobulins are proteins that are present in the serum and in the vertebrate tissues and bind specifically to foreign molecules (antigens), generating an immune response (Alarcón et al., 2000).